Influence of non-sinusoidal power supply on the performance of a single-phase capacitor induction motor - Alyozbaky, Omar Sharaf Al-deen; Ab‐Kadir, Mohd Zainal Abidin (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Harmonic is seen to be an important factor that can influence the performance of different electrical appliances. Earlier studies have regarded the non-sinusoidal power supply as the major source of the harmonic in the induction motors. In this paper, the researcher compared the results generated by a single-phase capacitor induction motor (SIM) using the sinusoidal and non-sinusoidal power supplies. The results in the study could help in comprehensively understanding the impact of the harmonic on the effective performance of the SIM machines when they were powered using a non-sinusoidal power supply. Here, the performance of the SIM when subjected to a maximum load or non-load condition were studied and determined. Furthermore, numerous experimental work was presented to validate the results of the SIM. Power analyses and spectral analysis indicated the actual difference in the overall harmonic wave distortion. It was seen that the current load increased to 89% (i.e., an increase of 11%) when the motor working from the non-sinusoidal source. This investigation highlighted the direct impact of the non-sinusoidal power source on the properties and components of the SIM machine. The vibrations measured under varying conditions and compared the results for the 2 types of power supplies.